2018
DOI: 10.1002/clc.23039
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular thrombosis in acute anterior myocardial infarction: Evaluation of hospital mortality, thromboembolism, and bleeding

Abstract: Among patients hospitalized with anterior STEMI, presence of LVT is associated with increased thromboembolic events, average length of hospital stay and average cost of hospitalization. However, it is not associated with increased in-hospital mortality or bleeding events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…NIS is the largest database of hospital inpatient stays in the United States (US), generated by the Agency for Healthcare Research and Quality (AHRQ). This database accounts for approximately up to 8 million discharges each year; and has been used in the past for ascertainment, tracking, and assessment of national trends in health care provision, access, major procedures related outcomes, disparity of care, hospitalizations rates, and analysis of health care economics and quality control measures . Each individual hospitalization in NIS is deidentified and kept as a unique entry with one primary discharge diagnosis and < 29 secondary diagnoses during that hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…NIS is the largest database of hospital inpatient stays in the United States (US), generated by the Agency for Healthcare Research and Quality (AHRQ). This database accounts for approximately up to 8 million discharges each year; and has been used in the past for ascertainment, tracking, and assessment of national trends in health care provision, access, major procedures related outcomes, disparity of care, hospitalizations rates, and analysis of health care economics and quality control measures . Each individual hospitalization in NIS is deidentified and kept as a unique entry with one primary discharge diagnosis and < 29 secondary diagnoses during that hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…В большинстве случаев при переднем ИМ инфаркт-связанной является передняя межжелудочковая артерия, на зону кровоснабжения которой приходится от 45 до 55 % миокарда левого желудочка (ЛЖ). При передней локализации ИМ часто возникают такие осложнения, как формирование аневризмы и образование тромба в ЛЖ [23].…”
Section: Discussionunclassified
“…We read with great interest the study by Ram et al They concluded in their study that patients with left ventricular thrombus (LVT) postanterior ST-segment elevation myocardial infarction (STEMI) was associated with increased in-hospital thromboembolic events and length of hospital stay, but not in-hospital mortality or bleeding risks compared to those without LVT formation. 1 They also reported a low incidence of LVT in anterior STEMI, which is of interest given the considerable sample size. However, we are concerned if this may limit the generalizability of the results.…”
Section: Surprisingly Low Incidence Of Left Ventricular Thrombosis Inmentioning
confidence: 90%